Learners’ User Experience Assessment of a Serious Game for Social Innovation Education - Schorer, Antonia; Protopsaltis, Aristidis (Proceedings of the 15th European Conference on Game Based Learning ECGBL 2021, 2021)
The use of serious games and game - based learning to develop new skills and knowledge in the context of social innovation education is a new and a promising endeavour. Social innovation education supports the empowerment and activation of students as social change makers. At the same time, the active engagem ent in socially impacted projects and activities enhances s elf - efficacy and promotes a positive emotional learning experience through game - based learning. Serious games are an opportunity for players - and learners - to demonstrate the impact of their actions in the creation and implementation of social innovation projects by working on emerging and real - world problems in a protected environment. To be able to achieve the educational goals of the game, the user experience of the learner during the game and learning process is crucial. A positive learning experience and appreci ation of the game, for instance in terms of usability and playability, will lead to more promising results than negative assessments. With the purpose of drawing conclusions in this context, the objective of this paper is to present the results of the user experience empirical analysis of learners in the NEMESIS Serious Games for Social Innovation. The game, based on an adventure and open - world game, introduces social innovation to students. This is achieved by bringing the player to NEMESIS City with the a im of increasing the well - being of the inhabitants with his "social innovation power". There, the player gets the opportunity to work on new problems and implement social innovation projects in collaboration with non - player characters (teachers, social inn ovators, parents’ , and other stakeholders) in order to be rewarded with happiness points for the city. The evaluation of the game focuses on usability/ playability, narratives, play engrossment, enjoyment, creative freedom, personal gratification, visual a esthetics and learning success of the game - based social innovation education approach. <br
Keywords: Serious Games; Game-based Learning; Social Innovation Education; Sustainable Development Goals; User Experience